(untitled) (Proceedings of International Educators Conference, 2024)
This article deals with the usage of task-based and project-based methods in foreign language teaching. The offering methods help the teacher to create a unique foreign language learning experience in almost every class, provided he/she is aware of what options are possible for their use and how to customize them in a particular teaching learning situation.